Genotype by environment interaction for growth traits of families of Acacia melanoxylon based on BLUP and GGE biplot - Ruan, Shao-Ning; Chen, Liu-Ben; Zhang, Bo; Zhang, Wei-Hao; Ding, Guo-Chang; Cao, Guang-Qiu; Ye, Long-Tai; He, Shi-Bin; Shen, Dong-Yang; Yan, Qiang (Frontiers in Plant Science, 2025)
Acacia melanoxylon is a high-quality timber species renowned for its superior heartwood and wide global use. To assess its stability, adaptability, and productivity in Fujian Province, China, a regional trial involving 47 A. melanoxylon families was conducted across four sites. The study utilized best linear unbiased prediction (BLUP) breeding values were estimated using 5-year-old diameter at breast height (DBH) and tree height data, and genotype plus genotype-by-environment (GGE) biplots were used to evaluate families and trial sites. The biplot generated based on BLUP values for DBH revealed that the four trial sites clustered into two groups. Group 1 comprised sites ZX (Zhangpu Zhongxi State-owned Forest Farm, Zhangpu County), LX (Quanzhou Luoxi State-owned Forest Farm, Quanzhou City), and XQ (Nanping Xiqin Teaching Forest Farm, Nanping City), while Group 2 included site LS (Nan’an Luoshan State-owned Forest Farm, Nan’an City). Sites LX and XQ showed strong positive correlations with each other and moderate correlations with ZX, indicating similar family rankings. In contrast, LX was negatively correlated with LS, reflecting opposing trends in genotype performance. Site ZX exhibited high discriminative power and representativeness, identifying it as the most effective location for evaluating families. Families 38, 35, 9, 17, and 24 demonstrated a combination of high yield and stability, underscoring their potential for extensive cultivation. The measurement of DBH is more cost-effective and accurate compared to tree height, and it aligns with our breeding objectives. Therefore, this study primarily focused on DBH for selection, and the results provide a theoretical foundation for promoting Acacia melanoxylon in Fujian Province.